Day shift - Harris, Charlaine (Harris, Charlaine. Midnight, Texas novels, 2015)
"There is no such thing as bad publicity, except in Midnight, Texas, where the residents like to keep to themselves. Even in a town full of secretive people, Olivia Charity is an enigma. She lives with the vampire Lemuel, but no one knows what she does; they only know that she's beautiful and dangerous. Psychic Manfred Bernardo finds out just how dangerous when he goes on a working weekend to Dallas and sees Olivia there with a couple who are both found dead the next day. To make matters worse, one of Manfred's regular and very wealthy clients dies during a reading. Manfred returns from Dallas embroiled in scandal and hounded by the press. He turns to Olivia for help; somehow he knows that the mysterious Olivia can get things back to normal. As normal as things get in Midnight"--